2015
DOI: 10.1103/physreva.92.042107
|View full text |Cite
|
Sign up to set email alerts
|

Generation of quantum steering and interferometric power in the dynamical Casimir effect

Abstract: We analyze the role of the dynamical Casimir effect as a resource for quantum technologies, such as quantum cryptography and quantum metrology. In particular, we consider the generation of Einstein-Podolsky-Rosen steering and Gaussian interferometric power, two useful forms of asymmetric quantum correlations, in superconducting waveguides modulated by superconducting quantum interferometric devices. We show that while a certain value of squeezing is required to overcome thermal noise and give rise to steering,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…The DCE can be explained qualitatively as a particular kind of the parametric amplification of quantum vacuum fluctuations in systems with time-dependent parameters leading to photon generation. In addition to the theoretical investigations on the issue of particle generation via the DCE in a large variety of systems, ranging from cosmology to non-stationary cavity * motazedifard.ali@gmail.com † a dalafi@sbu.ac.ir ‡ mhnaderi@sci.ui.ac.ir § rokni@sci.ui.ac.ir QED [11], various theoretical schemes for practical applications of the DCE have been suggested, including generation of photons with nonclassical properties [12][13][14], generation of atomic squeezed sates [15], generation of multipartite entanglement in cavity networks [16], and generation of EPR quantum steering and Gaussian interferometric power [17]. Most of the schemes proposed until now to realize the DCE can be roughly separated into two categories: (a) the schemes based on the real mechanical motion of boundaries, e.g., mirrors of a cavity, a mechanism referred to as motion-induced DCE (MIDCE) in the literature [18]; and (b) the schemes based on the parametric amplification of vacuum fluctuations in media without moving boundaries, a process which is a kind of imitation of boundary motion and known as parametric DCE (PDCE) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The DCE can be explained qualitatively as a particular kind of the parametric amplification of quantum vacuum fluctuations in systems with time-dependent parameters leading to photon generation. In addition to the theoretical investigations on the issue of particle generation via the DCE in a large variety of systems, ranging from cosmology to non-stationary cavity * motazedifard.ali@gmail.com † a dalafi@sbu.ac.ir ‡ mhnaderi@sci.ui.ac.ir § rokni@sci.ui.ac.ir QED [11], various theoretical schemes for practical applications of the DCE have been suggested, including generation of photons with nonclassical properties [12][13][14], generation of atomic squeezed sates [15], generation of multipartite entanglement in cavity networks [16], and generation of EPR quantum steering and Gaussian interferometric power [17]. Most of the schemes proposed until now to realize the DCE can be roughly separated into two categories: (a) the schemes based on the real mechanical motion of boundaries, e.g., mirrors of a cavity, a mechanism referred to as motion-induced DCE (MIDCE) in the literature [18]; and (b) the schemes based on the parametric amplification of vacuum fluctuations in media without moving boundaries, a process which is a kind of imitation of boundary motion and known as parametric DCE (PDCE) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of relativistic motion (of an uncharged, apolar object) to produce nonclassical radiation from the vacuum [12] provides a strong theoretical motivation to study the DCE. In addition, the quantum nature of the radiation produced has led to investigations of its utility for a wide variety of quantum information tasks such as entanglement generation [13][14][15][16][17][18], the generation of quantum discord [19], the production of cluster states for quantum computation [20], the performance of multipartite quantum gates [21,22], quantum steering [23] and quantum communication [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the dynamical Casimir effect (DCE), produced by the modulation of the boundary conditions of the electromagnetic field at relativistic speeds, has been observed in superconducting devices [15][16][17]. Along these lines, it has been shown that DCE radiation possesses several forms of quantum correlations [18][19][20][21][22] that can be transferred to superconducting qubits [23,24]. A related phenomenon is the Unruh effect, where an accelerated detector in vacuum should detect thermal radiation [25,26].…”
mentioning
confidence: 99%